Simulated infection alters the behavior of pair bonded songbirds and their healthy neighbors. (23rd February 2023) - Love, Ashley C; Anthony, Anna C; Nash, Aimee; Campos-Melara, Angel; Kodali, Jahnavi; DuRant, Sarah E
Abstract: While infection and perceived infection risk can influence social and reproductive behavior in several taxa, relatively little is known about how infection specifically affects pair bond behaviors. Some pair bond maintenance behaviors may be costly to maintain during infection, and infection could promote avoidance behaviors within an established pair. Many species exhibiting pair bonds are part of larger social groups, and behavioral shifts in established pairs can result in altered extra-pair contact rates that could also shape disease transmission. Using captive zebra finches ( Taeniopygia guttata ), we examined how an immune challenge with lipopolysaccharide (LPS) influences activity, social behavior, and pair bond maintenance behaviors in established pairs and their healthy neighbors. We observed shifts in individual and pair maintenance behaviors in both immune-challenged pairs and healthy pairs exposed to a social cue of infection (sick conspecifics). Specifically, LPS-challenged birds decreased activity and social interaction attempts relative to control birds, consistent with LPS-induced sickness behavior. LPS-challenged birds also increased the frequency of clumping (perching together in bodily contact) between individuals within a pair. Healthy birds exposed to immune-challenged conspecifics decreased flight activity and increased self-preening, behaviors which could function to limit infection risk. Exploring how both infection and the perceived risk of infection shape behaviors within and among paired individuals will increase our understanding of the role of social behaviors in shaping disease dynamics. Abstract : Being sick or being around others that are sick can alter how individuals interact. Sick zebra finches become less active and spend more time huddling beside their mate, which might help them maintain higher body temperatures that can better fight off an infection. Healthy birds viewing sick neighbors reduce their activity and clean their feathers more frequently, presumably to lower their risk of infection and limit the spread of disease.